Neurophysiology for predicting good and poor neurological outcome at 12 and 72 h after cardiac arrest: The ProNeCA multicentre prospective study. (1st February 2020) - Scarpino, Maenia; Carrai, Riccardo; Lolli, Francesco; Lanzo, Giovanni; Spalletti, Maddalena; Valzania, Franco; Lombardi, Maria; Audenino, Daniela; Contardi, Sara; Celani, Maria Grazia; Marrelli, Alfonso; Mecarelli, Oriano; et al.
Abstract: Aims: To assess the accuracy of electroencephalogram (EEG) and somatosensory evoked potentials (SEPs) recorded at 12 and 72 h from resuscitation for predicting six-months neurological outcome in patients who are comatose after cardiac arrest. Methods: Prospective multicentre prognostication study. EEG was classified according to the American Clinical Neurophysiology Society terminology. SEPs were graded according to the presence and amplitude of their cortical responses. Neurological outcome was defined as good (cerebral performance categories [CPC] 1–3) vs. poor (CPC 4–5). None of the patients underwent withdrawal of life-sustaining treatment. Results: A total of 351 patients were included, of whom 134 (38%) had good neurological outcome. At 12 h, a continuous, nearly continuous and low-voltage EEG pattern predicted good neurological outcome with 71[61–80]% sensitivity, while an isoelectric EEG and a bilaterally absent/absent-pathological amplitude (AA/AP) cortical SEP pattern predicted poor neurological outcome with 14[8–21]% and 59[50–68]% sensitivity, respectively. Specificity was 100[97–100]% for all predictors. At 72 h, both an isoelectric, suppression or burst-suppression pattern on EEG and an AA/AP SEP pattern predicted poor outcome with 100[97–100]% specificity. Their sensitivities were 63[55–70]% and 66[58–74]%, respectively. When EEG and SEPs were combined, sensitivity for poor outcome prediction increased to 79%. Conclusions: In comatose resuscitated patients, EEG and SEPs predicted good and poor neurological outcome respectively, with 100% specificity as early as 12 h after cardiac arrest. At 72 h after arrest, unfavourable EEG and SEP patterns predicted poor neurological outcome with 100% specificity and high sensitivity, which further increased after their combination.